Repurposing of the Nootropic Drug Vinpocetine as an Analgesic and Anti-Inflammatory Agent: Evidence in a Mouse Model of Superoxide Anion-Triggered Inflammation - Yuri Lourenco-Gonzalez; Victor Fattori; Talita P. Domiciano; Ana C. Rossaneis; Sergio M. Borghi; Tiago H. Zaninelli; Catia C. F. Bernardy; Jose C. Alves-Filho; Thiago M. Cunha; Fernando Q. Cunha; Rubia Casagrande; Waldiceu A. Verri (Mediators of Inflammation)
Clinically active drugs for the treatment of acute pain have their prescription limited due to the significant side effects they induce. An increase in reactive oxygen species (ROS) has been linked to several conditions, including inflammation and pain processing. Therefore, new or repurposed drugs with the ability of reducing ROS-triggered responses are promising candidates for analgesic drugs. Vinpocetine is a clinically used nootropic drug with antioxidant, anti-inflammatory, and analgesic properties. However, the effects of vinpocetine have not been investigated in a model with a direct relationship between ROS, inflammation, and pain. Based on that, we aimed to investigate the effects of vinpocetine in a model of superoxide anion-induced pain and inflammation using potassium superoxide (KO2) as a superoxide anion donor to trigger inflammation and pain. In the KO2 model, vinpocetine dose-dependently reduced pain-like behaviors (spontaneous pain and hyperalgesia), paw edema, and neutrophil and mononuclear cell recruitment to the paw skin (assessed by H&E staining, fluorescence, and enzymatic assays) and to the peritoneal cavity. Vinpocetine also restored tissue endogenous antioxidant ability and Nrf2 and Ho-1 mRNA expression and reduced superoxide anion production and gp91phox mRNA expression. We also observed the inhibition of IκBα degradation by vinpocetine, which demonstrates a reduction in the activation of NF-κB explaining the diminished production of IL-33, IL-1β, and TNF-α. Collectively, our data show that vinpocetine alleviates pain and inflammation induced by KO2, which is a mouse model with a direct role of ROS in triggering pain and other inflammatory phenomena. Thus, the results suggest the repurposing of vinpocetine as an anti-inflammatory and analgesic drug.